The Effect of Simulating Virtual Scenes using Artificial Intelligence Techniques in Producing Various Media Materials - Mohamed, Ahmed Omar (Journal of Ecohumanism, 2024)
Our current era is witnessing continuous change and rapid development in various aspects of life, including technical development and scientific progress. Modern technologies like simulation and artificial intelligence (AI) significantly enhance media content creation and distribution in various ways: Content Creation: AI tools can generate scripts, edit videos, create animations, and produce music, allowing creators to streamline the production process and reduce costs. Personalization: AI algorithms analyze user preferences and behavior to deliver personalized content recommendations, improving user engagement and satisfaction. Simulations: Simulation technologies can create realistic virtual environments for training, gaming, and storytelling, providing immersive experiences for users. Quality Enhancement: AI can automatically enhance audio and video quality, detect errors or inconsistencies, and improve overall production value. Data Analysis: AI helps analyze audience data to inform content strategies, predict trends, and optimize marketing efforts. Simulation and AI are transforming media content by making it more efficient, engaging, and tailored to audiences. The study aims to identify the impact of using these modern technologies in the field of media, which includes the latest technological developments, by utilizing virtual viewer simulations through artificial intelligence techniques, and achieving the highest levels of awareness for producing various media materials. The research also addresses the key stages that a designer goes through and how we can benefit from the study to develop these stages in order to enhance the role of visual communication and interaction between the recipient and the sender through the use of digital media designed within the media content via artificial intelligence to convey the advertising message, and its role in influencing consumer motivations to attract and guide them in making decisions through artificial intelligence techniques that provide a clear vision of the design environment. The research highlights the importance of graphic design as an essential element in improving viewers’ experience of modern digital media and achieving a more realistic simulation, pointing to the development of the concept of simulation used in modern digital media and Computer-Generated Image (CGI) techniques. This research also aims to explore the vital role that graphic design plays at every stage of the production of digital technologies to achieve a more realistic simulation of virtual scenes in digital media. Hence, the research problem the extent to which media content, in terms of form and substance, benefits from these modern technologies (simulation - Artificial intelligence) and the impact of these technologies in making media content more credible through their use. The research hypotheses: Has the media content become more attractive with the use of these technologies (simulation Artificial intelligence)? Has the media content become more shareable across different platforms in form and substance with the use of these technologies (simulation - Artificial intelligence)? Has the media content become more appealing with the use of these technologies (simulation - Artificial intelligence)? Has the media content become more effective in the visual communication process with the use of these technologies (simulation - Artificial intelligence)? Has the use of these technologies (simulation - Artificial intelligence) provided competitive advantages for various media outlets? Has the use of these technologies (simulation - Artificial intelligence) offered marketing and promotional advantages for various media outlets? What are the positives and negatives of these technologies (simulation - Artificial intelligence) in the media? The main aim of the research the extent to which media content, in terms of form and substance, benefits from modern technologies (simulation – Artificial intelligence) and the impact of these technologies on enriching, supporting, and developing media content to make it more competitive and credible through their use. The importance of research in studying the role and impact of modern technologies, such as virtual scene simulation, using artificial intelligence techniques to produce various types of media content. It emphasizes the role of these technologies in influencing different media outlets regarding competitive advantages, marketing, and promotion, as well as highlighting the positives and negatives of these technologies. The research methodology is based on the analytical description approach.